EFFECTIVENESS OF MOTHER NGO (MNGO) SCHEME AS A STRATEGIC CONCEPT IN RCH IN DISTRICTS DEHRADUN AND PAURI GARHWAL, UTTARAKHAND - Roy, D; Joshi, K; Dhasmana, S (Indian Journal of Community Health, 2013)
Background: Effective application of MNGO (RCH) concept has significantly and positively influenced the improved health scenario of the state and the scheme justifiably served as an innovative and strategic input to make available services accessible to the unserved/underserved population at far outreaches of the state of Uttarakhand. Methods: An observational, descriptive study was designed with a disadvantaged population of 119242 from select 427 villages of the districts of Dehradun and Pauri Garhwal to study trend of key RCH indicators for service utilization & effectiveness of MNGO Scheme. Community endorsed BCC, capacity building and prioritized RCH services as per CNA provided by FNGOs through community and clinic based approaches comprised the scheme components. Results: Implementation results showed a linear increase in proportion of beneficiaries for key RCH indicators over time (2000-09); difference of status for all indicators between baseline (2000-01) & project- end (2008-09) values was found statistically significant (p<0.05). Further, comparison of project end achievement data with corresponding DLHS data from study districts showed significant (p<0.05) difference; also, nominal impression (FGDs) yielded evidence of community ownership of the initiative. Conclusion: Trend of key RCH indicators, comparison of project-end achievement with concurrent available survey results and nominal impression (FGDs) from the beneficiaries provided ample evidence of effectiveness of MNGO (RCH) scheme as a community initiative in districts Dehradun and Pauri Garhwal.